Citizenship and globalization (2007)
The essay refers to the relationship between globalization and citizenship rights. In the first part, the author presents an approach to the concept of citizenship and then discusses the cosmopolitan theories which assume globalization as the advent of the global civil society. In the last part, the author points out the world levels of inequality to conclude on the restrictive character of some of the new rights in the society of information.